Economic impact of the use of agroecological innovations by small corn farmers in Tlaxcala and Oaxaca - Cuevas-Reyes, Venancio; Jolalpa-Barrera, Jos´é Luis; Sánchez-Toledano, Blanca I.; Borja-Bravo, Mercedes; Cadena-Iñiguez, Pedro (Revista Mexicana de Ciencias Agrícolas, 2025)
The agroecological transition of agricultural production is a medium-term process, so estimating the effect of using agroecological innovations through economic indicators can contribute to the identification of areas of opportunity and decision-making within the framework of this new paradigm. The objective was to estimate the economic effect of the use of agroecological innovations by small rainfed corn producers in Tlaxcala and Oaxaca, through economic indicators, during 2020 and 2021. The sample was non-probabilistic and aimed at 10 corn producers: five producers from Tlaxcala (G1) and five producers from Oaxaca (G2). The results showed that the groups are similar in their social and productive characteristics, they only differed (p< 0.05) in agricultural area. Three indicators that measure the economic effect of the use of technologies were obtained: change in production cost (CPC), change in yield (CY), and change in the cost of agrochemical use (CCAU). The CPC ranged from -3.1 to 14.6% for G1 and from -4.6 to 27.7% for G2; the CY was 12.8 and 6.8% for G1 and G2, respectively, and the CCAU from -15.6 to 2.2% for G1 and from -15.5 to 4.8% for G2. Obtaining the indicators can make it possible to identify producers with more sustainable food systems, analyze their components, and generate recommendations for replicating these systems.
Keywords: bioinputs; corn; peasant agriculture